2016
DOI: 10.1038/npjparkd.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Different PD-MCI criteria and risk of dementia in Parkinson’s disease: 4-year longitudinal study

Abstract: The Movement Disorder Society Task Force (MDS-TF) has proposed diagnostic criteria for mild cognitive impairment in Parkinson’s disease (PD-MCI). We hypothesized that the risk of dementia (PDD) varies across the different cutoff schemes allowed. A longitudinal study followed 121 non-demented PD patients for up to 4.5 years. In Part One, unique groups of patients were identified as PD-MCI at baseline using the MDS-TF requirement of two impaired cognitive test scores, with both scores classified as impaired at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 43 publications
6
66
2
1
Order By: Relevance
“…The highest percentages of PD patients with impairment (i.e., >2 SDs below control mean) on the individual neuropsychological tests were for TMT-B (20.2%) and TMT-A (19.6%). We also highlighted the clusters that sur- (Caviness et al, 2007;Muslimovic, Post, Speelman, & Schmand, 2005;Wang et al, 2015), the majority of our PD-MCI patients had multipledomain deficits (94.9%), similar to the studies using the MDS Task Force criteria (Goldman, Weis, Stebbins, Bernard, & Goetz, 2012;Wood et al, 2016). We also highlighted the clusters that sur- (Caviness et al, 2007;Muslimovic, Post, Speelman, & Schmand, 2005;Wang et al, 2015), the majority of our PD-MCI patients had multipledomain deficits (94.9%), similar to the studies using the MDS Task Force criteria (Goldman, Weis, Stebbins, Bernard, & Goetz, 2012;Wood et al, 2016).…”
Section: Cognitive Profile In Pd Patients and Healthy Controlssupporting
confidence: 75%
“…The highest percentages of PD patients with impairment (i.e., >2 SDs below control mean) on the individual neuropsychological tests were for TMT-B (20.2%) and TMT-A (19.6%). We also highlighted the clusters that sur- (Caviness et al, 2007;Muslimovic, Post, Speelman, & Schmand, 2005;Wang et al, 2015), the majority of our PD-MCI patients had multipledomain deficits (94.9%), similar to the studies using the MDS Task Force criteria (Goldman, Weis, Stebbins, Bernard, & Goetz, 2012;Wood et al, 2016). We also highlighted the clusters that sur- (Caviness et al, 2007;Muslimovic, Post, Speelman, & Schmand, 2005;Wang et al, 2015), the majority of our PD-MCI patients had multipledomain deficits (94.9%), similar to the studies using the MDS Task Force criteria (Goldman, Weis, Stebbins, Bernard, & Goetz, 2012;Wood et al, 2016).…”
Section: Cognitive Profile In Pd Patients and Healthy Controlssupporting
confidence: 75%
“…While the authors reported significantly lower quality of life scores with regard to physical health and interruptions to usual activities among PD-MCI caregivers, they mention that there was no difference in caregiver burden. They did not, however, report the actual levels of burden, but stated that the results were similar to those of Leroi et al [9] These two studies used level I criteria to establish PD-MCI status, whereas the current study employed the more comprehensive level II criteria, which has been shown to be suitable in terms of stability and increased risk of progression to PDD [4]. Also, level I criteria may underestimate the proportion of PD-MCI patients and thus misclassify some PD-MCI patients as PD-N [31].…”
Section: Discussionsupporting
confidence: 60%
“…The distribution of patients in these four groups varies markedly among different studies, depending on factors including the case selection procedures, the criteria applied, the study design (cross-sectional or longitudinal), and the cognitive measurement procedures utilized. A recent study, which attempted to define the optimal criteria for PD-MCI, found that impairment (>1.5 SD below the normative mean) on two tests within the same cognitive domain — rather than across different domains — was the best predictor of progression to dementia during the next 4 years 13 . As highlighted above, the separation between MCI and dementia hinges on whether the functional impact of cognitive impairment is ‘severe enough to impair daily life’, a criterion that is difficult to operationalize and requires an element of clinical judgement.…”
Section: Cognitive Syndromes In Pdmentioning
confidence: 99%